Management of central nervous system involvement in chronic lymphocytic leukaemia: a retrospective cohort of 30 patients. (11th November 2016) - Wanquet, Anne; Birsen, Rudy; Bonnet, Charlotte; Boubaya, Marouane; Choquet, Sylvain; Dupuis, Jehan; Lepretre, Stephane; Re, Daniel; Fahri, Jonathan; Michallet, Anne‐Sophie; Ysebaert, Loïc; Lemal, Richard; et al.
Summary: Central nervous system involvement (CNSi) is a rare and poorly reported complication of chronic lymphocytic leukaemia (CLL). Establishing cause and effect between the CLL and the neurological symptoms remains challenging. We have analysed a retrospective cohort of 30 CLL patients with CNSi, documented by lymphocytic infiltration either by flow cytometry of the cerebrospinal fluid (CSF; n  = 29) or CNS biopsy ( n  = 1). Neurological symptoms were heterogeneous. At the time of CNSi, less than half of the patients had a progressive CLL and 20 had never been treated for CLL. Initial treatment with fludarabine‐based immuno‐chemotherapy, with or without intra‐CSF therapy, led to durable response in eight out of nine untreated patients. In contrast, 50% patients receiving various prior treatments needed additional therapy within a median of 4 months (1–16). Ibrutinib led to complete response in 4/4 heavily pre‐treated patients. From CNSi, 5‐year overall survival was 72% and 48% for treatment‐naïve and previously treated patients respectively ( P  = 0·06); 5‐year progression‐free survival (PFS) was 43% and 0% ( P  = 0·125). 17p deletion was significantly associated with poor PFS ( P  = 0·006). CNSi may be the only sign of progression of CLL and should be considered an initiation criterion of systemic treatment. Prognosis seemed to be related to CLL characteristics rather than to CNSi itself.